Formación profesional de camponeses en una escuela en la amazonia brasileña - SOUSA, Romier da Paixão (Universidad de Murcia, 2022)
The perspective of this article is communicate about a scientific study and considerations con-cerning to Agroecological education and its practical results in a Brazilian Governmental Institu-tion - Federal Institute of Education, Science and Technology of Pará -IFPA- Campus Castanhal. It has been noticed advances towards agroecological education internalization at public institutes dedicated to knowledge production and share for the rural development, mainly at official edu-cation. However, practice at IFPA – Campus Castanhal has showed that establishing agroecologi-cal approach at an Institution like this depends, indeed, on an amount of interconnected factors. Thus, to set up agroecological principles do not need accurately settle an Agroecology Course. It has been also realized Principles of Agroecology, just as an interdisciplinary approach, it might be added to other courses from a methodological exchange through educational process.